MOTIVASI DAN SUMBER INFORMASI BERHUBUNGAN DENGAN PENCEGAHAN STROKE BERULANG - Mevi Lilipory; Magdalena Helena Pattipelohy; Yoan Susan Tuarissa (MOLUCCAS HEALTH JOURNAL, 2019)
Recurrent Stroke is a neurological disorder that occurs due to lack of blood supply to areas of the brain after previously having a stroke. Patients who have low motivation need to have the support of family because of the support or encouragement a family can strengthen and motivate the patient to achieve the expected goals.  The provision of information anticipation and planning that takes the patient and family after returning home, is an important part in health care in a comprehensive manner and should be done on each treatment plan of the patient.  The purpose of this study was to determine the relationship of motivation and a source of information with prevention of recurrent stroke in RSUD Dr. M. Haulussy Ambon. Research design this research uses observational analytic design with cross-sectional.  The number of samples in this study were 47 respondents.  Data collection using a questionnaire and the results are tested by using Chi-Square test value of p < 0.05 (p = 0.003) and showed that there is a significant relationship between motivation and the prevention of recurrent stroke in RSUD Dr. M. Haulussy Ambon and there was a significant relationship between source of information with prevention of recurrent stroke in RSUD Dr. M. Haulussy Ambon with the results of the Chi-Square test value of p < 0.05 (p = 0.000).  From this study it is suggested can be used as information in the add insight and knowledge in the field of health especially in providing motivation and information for people who have a stroke can prevent recurrent stroke.Keyword : Motivation, Source Of Information, The Prevention Of Recurrent Stroke